Exploration and Development of a C–H-Activated Route to Access the [1,2]Dithiolo[4,3-b]indole-3(4H)-thione Core and Related Derivatives - Asquith, Christopher R. M.; Konstantinova, Lidia S.; Tizzard, Graham J.; Laitinen, Tuomo; Coles, Simon J.; Rakitin, Oleg A.; Hilton, Stephen T. (Synlett, 2019)
A robust procedure for the production of [1,2]dithiolo[4,3-b]indole-3(4H)-thione analogues using a DABCO/S2Cl2 complex as a sulfur source via a C–H activated approach.
Keywords: indole; indole sulfides; sulfur-nitrogen heterocycles; fused 3H-1,2-dithiole-3-thiones; C–H activation; disulfur dichloride